Prosocialness and Happiness in Chilean Student Teachers - Mieres-Chacaltana, Manuel; Salvo-Garrido, Sonia; Denegri, Marianela (Frontiers in Psychology, 2021)
The aim of the study was to evaluate the relation between prosocialness and happiness in a sample of student teachers (N=224, age=21.42). Adapted versions of a prosocialness scale and another on happiness were used. A structural equations model was estimated that presented a suitable fit (CFI=0.951; TLI=0.944 and RMSEA=0.065). The results yielded a positive relation between prosocialness and happiness. Its implications for initial teacher training are discussed.